Verminosis management of sheep in the farming family in Pinheiro Machado, Brazil - Traversa Tejero, Ignacio Pablo; Gonçalves Lopes, Rafael (Agronomía Mesoamericana, 2017)
The objective of this research was to analyze the control methods of ovine verminosis in the agriculture family of Pinheiro Machado municipality, located in the state of Rio Grande do Sul (RS), Brazil. In 2015, available information regarding agriculture on anthelmintics was collected by conducting interviews and by applying questionnaires to 32 sheep breeders. There were 11 active principles and 34 commercial names of medications registered for deworming. All the producers used anti-parasite drugs to control sheep verminosis, and 90% of the producers applied vermifuges without taking into account technical criteria. Only 1.8% gave a suitable destination to medical devices packages. Sheep farmers increased the frequency and dose usage of antiparasitic drugs, the aforementioned shows as consequences an increase in parasitic resistance to deworms and an environmental impact. In order to increase production and reduce chemicals that are harmful to the environment, sheep breeders shall use phytotherapy, homeopathy, biological control, rotational grazing, and the Famacha method.